CONTRIBUTION OF K.K. SAMRIN TO THE FORMATION OF THE KHAKASS WRITING SYSTEM (in 1920-1930-s) - Mamysheva Elena Petrovna,; Yuyukina Lyudmila Victorovna, (Scientific Journal of Pedagogy and Economics, 2021)
Russia, that was formed as a multi-ethnic and multilingual state, faced urgent question of the spiritual revival of the peoples, who were involved in the process of rapid assimilation at the beginning of the XXI century. National minorities and indigenous peoples have lost their main features of their ethnicity. Among them is disappearance of the native language. The national revival of any nation is inconceivable without the functioning of its mother language. Writing is the main means of fixing, preserving, development of the language and the most significant form of its social functioning. In this regard, it becomes relevant to address the origins of the Soviet writing of the peoples of Siberia. The article deals with the complex process of formation of writing system in Republic of Khakassia. The novelty of the research can be seen in attempts to realize the results of alphabetization through the prism of the biography of one of the participants in the creation of the Khakass script in the 1920s and 1930s. In this regard, K. K. Samrin's contribution to the development of the Khakass language, creation of the alphabet and national literature is revealed. The results of the research can be used in planning and forecasting of language development of minority languages.